2022
DOI: 10.1038/s12276-022-00756-6
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic synovial fibroblasts are modulated by NBCn1 as a potential target in rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is an autoimmune disease characterized by aggressive fibroblast-like synoviocytes (FLSs) and pannus formation. Various therapeutic strategies have been developed against inflammatory cytokines in RA in recent decades. Based on the migratory features of FLSs, we examined whether modulation of the migratory module attenuates RA severity. In this study, inflamed synovial fluid-stimulated FLSs exhibited enhanced migration and migratory apparatus expression, and sodium bicarbonate cotransp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…NBC activity is modulated by various cellular stimulants, such as ROS [ 18 ], acidic [ 49 ], hypoxia [ 50 ], and inflammatory cytokines [ 49 ]. Our previous study showed that HTK-induced arrest mediated more acidic intracellular circumstances through the involvement of sodium-potassium-chloride cotransporter Nkcc1 and chloride-bicarbonate exchanger Slc26a6 in the db/db diabetic mouse model’s heart than in wild-type mice during reperfusion [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NBC activity is modulated by various cellular stimulants, such as ROS [ 18 ], acidic [ 49 ], hypoxia [ 50 ], and inflammatory cytokines [ 49 ]. Our previous study showed that HTK-induced arrest mediated more acidic intracellular circumstances through the involvement of sodium-potassium-chloride cotransporter Nkcc1 and chloride-bicarbonate exchanger Slc26a6 in the db/db diabetic mouse model’s heart than in wild-type mice during reperfusion [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ras signaling is involved in migration in various cellular systems, such as vascular smooth muscle cells, endothelial cells, and several cancers [ 54 , 55 , 56 , 57 ]. In addition, NBCn is known to provide a migratory module in various cell types, such as vascular smooth muscle cells, breast cancers, and synoviocytes [ 49 , 58 , 59 ]. Currently, there is no direct evidence for an association between Ras and NBCn.…”
Section: Discussionmentioning
confidence: 99%
“…SLC, solute carrier; Glu, glutamate; Asp, aspartate; Ala, alanine; Asn, asparagine; Cys, cysteine; His, histidine; Ser, Serine; Zn, zinc; Cd, Cadmium; Mn, Magnesium; T3, Triiodothyronine; T4, Thyroxine; L-DOPA, L-Dopamine; AA, amino acids; BCH, 2-aminobicyclo-(2, 2, 1)-heptane-2-carboxylic acid. (12,42). Upon siRNA knockdown of SLC4A4, RA FLS were found to be more invasive but with unchanged migration compared to control siRNA (12).…”
Section: Slc4 Bicarbonate Transporter Familymentioning
confidence: 94%
“…In the context of these transporters playing a known role in migration of other cell types, one group has investigated the role of bicarbonate transporters on RA FLS migrations. Upon testing various genes of the SLC4 family, SLC4A7 (also known as NBCn1) was shown to be significantly increased in RA FLS upon TNF-a expression as compared to OA FLS ( 42 ). As a result, TNF stimulation significantly increased migration.…”
Section: Slc4 Bicarbonate Transporter Familymentioning
confidence: 99%
“…Rheumatoid arthritis fibroblast-like synoviocytes (RA-FLS) lead to the proliferation of synovial membrane, inflammatory reactions, extensive angiogenesis, the disintegration of cartilage matrix, and destruction of bones by producing abundant pro-inflammatory cytokines and chemokines ( Bartok and Firestein, 2010 ; Aldridge et al, 2020 ; Bai et al, 2022 ; Ji et al, 2022 ); Figure 1 ). RA-FLS continuously produces many inflammatory factors like IL-6, IL-1β, TNF-α, vascular endothelial growth factor (VEGF), and matrix metalloproteinases (MMPs).…”
Section: The Pathogenesis Of Rheumatoid Arthritismentioning
confidence: 99%